Course of psychotic experiences and disorders among apprentice traditional health practitioners in rural South Africa: 3-year follow-up study - van der Zeijst, Martine C. E.; Veling, Wim; Makhathini, Elliot M.; Mbatha, Ndukuzakhe D.; Shabalala, Sinethemba S.; van Hoeken, Daphne; Susser, Ezra; Burns, Jonathan K.; Hoek, Hans W. (Frontiers in Psychiatry, 2022)
Background: Culture is inevitably linked with the experience, interpretation and course of what modern biomedicine understands to be psychotic symptoms. However, data on psychoses in low- and middle-income countries are sparse. Our previous study showed that psychotic and mood-related experiences, symptoms and disorders are common among individuals who had received the ancestral calling to become a traditional health practitioner (THP) in rural KwaZulu-Natal, South Africa. Our related ethnographic study suggested that ukuthwasa (the training to become a THP) may positively moderate these calling-related symptoms. As far as we know, no research has been conducted into the course of psychiatric symptoms among apprentice THPs. Objective: We studied the course of psychotic experiences, symptoms and disorders among apprentice THPs. We also assessed their level of functioning and expanded our knowledge on ukuthwasa. Method: We performed a 3-year follow-up of a baseline sample of apprentice THPs (n=48). Psychiatric assessments (CAPE, SCAN), assessment of functioning (WHODAS) and a semi-structured qualitative questionnaire were completed for 42 individuals. Results: At 3-year follow-up, psychotic experiences were associated with significantly less distress and there was a reduction in frequency of psychotic symptoms compared to baseline. The number of participants with psychotic disorders had decreased from 7 (17%) to 4 (10%). Six out of seven participants (86%) with a psychotic disorder at baseline no longer had a psychiatric diagnosis at follow-up. Although the mean level of disability among the (apprentice) THPs corresponded with the 78th percentile found in the general population, 37 participants (88%) reported no or mild disability. Forty-one participants (98%) reported that ukuthwasa had positively influenced their psychiatric symptoms. Conclusion: In rural KwaZulu-Natal, psychotic experiences, symptoms and disorders have a benign course in most individuals who are undergoing the process of becoming a THP. Ukuthwasa may be an effective, culturally sanctioned, healing intervention for some selected individuals, potentially because it reframes distressing experiences into positive and highly-valued experiences, reduces stigma, and enhances social empowerment and identity construction. This implies that cultural and spiritual interventions can have a positive influence on the course of psychosis.